Characteristic pattern of chromosomal gains and losses in primary large B-cell lymphomas of the gastrointestinal tract - Barth, Thomas F. E.; Döhner, Hartmut; Werner, Claudius Alexander; Stilgenbauer, Stephan; Schlotter, Magdalena; Pawlita, Michael; Lichter, Peter; Möller, Peter; Bentz, Martin (Blood, 1998)
In contrast to low-grade B-cell lymphomas originating in the gastrointestinal (GI) tract, only few cytogenetic data are available for the large cell, highly malignant variants. We studied 31 large B-cell lymphomas of the GI tract by comparative genomic hybridization (CGH) and fluorescence in situ hybridization using specific DNA probes (FISH). The most frequent aberrations were gains of all or of parts of chromosomes 11 (11 cases), 12 (9 cases), 1q (4 cases), and 3q (4 cases). Losses of parts of chromosome 6q and of parts of the short arm of chromosome 17 (6 cases each) were found most frequently. In four cases a total of seven high-level DNA amplifications was detected. In two of these cases, involvement of specific protooncogenes (RELand MYC) was shown. Some genetic aberrations seemed to be associated with an inferior clinical course: patients with ≥2 aberrations had a significantly shorter median survival. Furthermore, all patients with gains of all or parts of chromosome arm 1q and with high-level DNA amplifications as well as seven of nine patients with gains of all or parts of chromosome 12 died of lymphoma. In conclusion, the pattern of chromosomal gains and losses in large B-cell lymphomas was different from data reported for low-grade (MALT) lymphomas of the stomach and bowel, especially with respect to the high incidence of partial gains of chromosome arm 11q and of all or parts of chromosome 12 and the low frequency of polysomy 3. In addition, our data suggest that chromosomal gains and losses detected by CGH and FISH may predict for the outcome of patients with this tumor entity.
Gesehen am 03.04.2024
Elektronische Reproduktion der Druck-Ausgabe 14. Dezember 2020, Artikelversion 14. Detember 2020